PENGARUH INDEPENDENSI, PENGALAMAN KERJA, SKEPTISME PROFESIONAL AUDITOR, FEE AUDIT DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK (KAP) DI PROVINSI BALI Ni Kadek Mariyati1, Ni Kadek Sinarwati2 1,2 Program Studi S1 Akuntan - Ni Kadek Mariyati; Ni Kadek Sinarwati (Universitas Pendidikan Ganesha, 2023)
Audit quality is very important in order to maintain the trust of clients and those who use audit reports. The profession of public accounting is a profession of public trust so that people obtain reliable financial information as a basis for decision making. The purpose of the research is to determine the effec of independence, work experience, professional skeptism, audit fee and time budget pressure on audit quality at Public Accountants in Bali. This research used questionnaire for collecting data and found 55 respondents that met the criteria. This study used multiple linear regression analysis for hypothesis testing. The results of this study indicate variable independence, work experience and professional skeptism auditor have positive effect on audit quality but audit fee and time budget pressure dont have significant effect on audit quality.